Kelelahan pada Pasien Congestive Heart Failure - Setianingsih, Mauludina Putri; Hastuti, Yuni Dwi (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: Fatigue is a characteristic symptom and is often found in CHF patients and has a negative effect on daily activities, disease prognosis, and patient's quality of life. However, fatigue is a common symptom that is often overlooked and ignored. Limited study explored fatigue in CHF patients. The aim of this study was to explore fatigue in CHF patients. Methods: The research design is a descriptive survey. The total research sample is 85 respondents. Data were taken using a Multidimensional Assessment Fatigue (MAF) questionnaire with univariate data analysis in the form of a frequency distribution. Respondents involved in the study were patients aged >18 years who suffered from CHF based on a doctor's diagnosis and confirmed by medical records. Results: The majority of respondents are elderly with female gender, work as household workers, and heve income less than Rp1,500,000/month. Examination of vital signs performed on the majority of CHF patients showed normal temperature (36.5℃ - 37.5℃), pre-hypertensive blood pressure (120/80 - 139/89 mmHg), normal pulse (60-100x/min), and normal respiratory rate (12-20x/minute). Most patients have a CHF duration of 1–3 years, and are in grades 2 and 3 based on the New York Association (NYHA) classification. The results of this study were 65.9% of CHF patients experienced moderate fatigue, 17.6% severe fatigue, and 16.5% mild fatigue. Conclusion: Health services can consider efforts to improve the quality of nursing services in overcoming or minimizing fatigue experienced by CHF patients. These efforts can be a therapy, evidence-based health education, or fatigue monitoring for preventing a worsening of disease prognosis and improving the patient's quality of life. Keywords: CHF, Fatigue, Multidimensional Assesment Fatigue.